A scientometric analysis of ICADL conference papers. - Lim, Cheng Hong. (2010)
Academic institutes have been using the concept of scientometrics for the purpose of evaluating the research performance of their departments. The result will be used for measuring the progress of the departments and institutes as well as being used as a factor in decision making for managing funds. Scientometric analysis of the International Conference on Asian Digital libraries (ICADL) was performed from 2000 to 2006.Through the combination of the native XML database(Sedna) and XQuery language, the various parameters of authorship patterns, yearly submission of journals,average lenght of articles and number of citations are examined.The concepts of Collaboration Coefficient, Collaborative Index and Degree of Collaboration are used in this study to get a better picture of the distribution of the authorships, quality of papers and the measurement of the mutliple-authored papers in the ICADL. Using the ranking methods of First Author, Whole Counting and Fractional Counting, this study will attempt to find the author who has been contributing most to the ICADL during the seven years.